Multipacting in a coaxial coupler with bias voltage for SRF operation with a large beam current. (30th September 2016) - Liu, Z.-K.; Wang, Ch.; Chang, F.-Y.; Chang, L.-H.; Chang, M.-H.; Chen, L.-J.; Chung, F.-T.; Lin, M.-C.; Lo, C.-H.; Tsai, C.-L.; Tsai, M.-H.; Yeh, M.-S.; et al.
Abstract: A superconducting radio-frequency (SRF) module is commonly used for a high-energy accelerator; its purpose is to provide energy to the particle beam. Because of the low power dissipation and smaller impedance of a higher-order mode for this module, it can provide more power to the particle beam with better stability through decreasing the couple bunch instability. A RF coupler is necessary to transfer the high power from a RF generator to the cavity. A coupler of coaxial type is a common choice. With high-power operation, it might suffer from multipacting, which is a resonance phenomenon due to re-emission of secondary electrons. Applying a bias voltage between inner and outer conductors of the coaxial coupler might increase or decrease the strength of the multipacting effect. We studied the effect of a bias voltage on multipacting using numerical simulation to track the motion of the electrons. The simulation results and an application for SRF operation with a large beam current are presented in this paper.